AI-Assisted Writing Tools and the Perceptions of Fairness in University Writing Courses and Assessments: An Analysis through Equity Theory - Hamid Issafi; Aziz Ouladhadda (Journal of English Language Teaching and Linguistics, 2024)
Nowadays, with the rapid breakthroughs in software and AI technology, the growing use of AI among university students has sparked considerable debate. In this context, the present research seeks to understand the impact of AI-assisted writing tools on students' perceptions of fairness, academic integrity, and their learning outcomes. An exploratory sequential design was used in this study, beginning with two focus groups to gather qualitative insights that informed the development of a 22-item survey. The survey was then administered to 107 students from the English departments at three institutions of Mohamed V University: FLSH, FSE, and ENS. The results indicate that AI use significantly affects students’ perceptions of fair assessment, with many viewing it as a tool that enhances work quality and academic grades. However, the use of AI is also associated with reduced motivation, lower willingness to invest effort, and diminished self-confidence. To address these challenges, participants suggested alternative assessment methods, including oral exams, tasks that emphasize critical thinking and creativity, and group work. By Analyzing these findings through the lens of Equity Theory and in light of existing research, this study offers insights into the evolving dynamics of fairness and academic integrity in the era of AI. It also offers recommendations for adapting assessment practices to maintain equity and integrity in higher education.